2020
DOI: 10.1002/anie.201912909
|View full text |Cite
|
Sign up to set email alerts
|

Rapid One‐Step Synthesis and Compaction of High‐Performance n‐Type Mg3Sb2 Thermoelectrics

Abstract: n‐type Mg3Sb2‐based compounds have emerged as a promising class of low‐cost thermoelectric materials due to their extraordinary performance at low and intermediate temperatures. However, so far, high thermoelectric performance has merely been reported in n‐type Mg3Sb2‐Mg3Bi2 alloys with a large amount of Bi. Moreover, current synthesis methods of n‐type Mg3Sb2 bulk thermoelectrics involve multi‐step processes that are time‐ and energy‐consuming. Herein, we report a fast and straightforward approach to fabricat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 52 publications
1
32
1
Order By: Relevance
“…With the experimental data of the Nd-, Tm-, and Y-doped samples, we can compare the results with those of the reported Te-and Sc-doped samples prepared using a similar synthesis method. [30] It is found that n-type Nddoped and Tm-doped Mg 3 Sb 2 samples show slightly lower electron concentrations than those of the Y-doped samples but higher electron concentrations than those of Sc-doped and Te-doped samples (see Figure 2c), which is consistent with the theoretical calculation. The room temperature electron concentrations of ntype Mg 3.5 Nd y Sb 2 samples vary from 1.46 × 10 19 (y = 0.01) to 3.17 × 10 19 cm −3 (y = 0.03), while the electron concentrations vary from 7.32 × 10 18 to 2.36 × 10 19 cm −3 in Mg 3.5 Tm y Sb 2 samples.…”
Section: Doi: 101002/advs202002867supporting
confidence: 87%
See 4 more Smart Citations
“…With the experimental data of the Nd-, Tm-, and Y-doped samples, we can compare the results with those of the reported Te-and Sc-doped samples prepared using a similar synthesis method. [30] It is found that n-type Nddoped and Tm-doped Mg 3 Sb 2 samples show slightly lower electron concentrations than those of the Y-doped samples but higher electron concentrations than those of Sc-doped and Te-doped samples (see Figure 2c), which is consistent with the theoretical calculation. The room temperature electron concentrations of ntype Mg 3.5 Nd y Sb 2 samples vary from 1.46 × 10 19 (y = 0.01) to 3.17 × 10 19 cm −3 (y = 0.03), while the electron concentrations vary from 7.32 × 10 18 to 2.36 × 10 19 cm −3 in Mg 3.5 Tm y Sb 2 samples.…”
Section: Doi: 101002/advs202002867supporting
confidence: 87%
“…Although the Nd-doped samples have been sintered at a high temperature of 800°C followed by annealing at 615°C under the Mg-rich environment [11] (see the Experimental Section) to minimize the grain boundary scattering, the electron mobility of Nd-doped Mg 3 Sb 2 samples still shows a temperature dependence of T 1.5 at low temperatures. This is very different from the Y-doped, Sc-doped, [30] or Te-doped [30] samples synthesized using a similar method, which show dominant acoustic phonon scattering at low temperatures ( Figure S14, Supporting Information). The increasing temperature dependence of the mobility at low temperatures results in poor room-temperature electron mobility (≈20.8-32.3 cm 2 V −1 s −1 ) of Nd-doped samples in comparison with those of Te-doped samples (≈51.0-73.8 cm 2 V −1 s −1 ).…”
Section: Doi: 101002/advs202002867mentioning
confidence: 64%
See 3 more Smart Citations